The Influence of Perceived Ease of Use and Security on QRIS Usage Decisions Among the Community in Lampung Province - Anisa Safitri; Yuniarti Fihartini (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Payment system developments brought about by technological advancements to date have resulted in a variety of cashless transactions, including card-based and application-based (server) electronic money. Bank Indonesia launched QRIS (Quick Response Code Indonesian Standard), an application-based non-cash payment system that addresses community demands. Finding out how perceived ease of use and security affect QRIS usage decisions in the Lampung Province Community is the goal of this study. This study is quantitative and employs a survey approach, distributing a questionnaire to 140 Lampung Province residents who have used QRIS to make payments. The study's findings suggest that decisions about usage are significantly influenced by perceivedease of use and security in transactions.